The Effect of Combining Hydrotherapy and Sunbathing Therapy on Blood Pressure in Elderly Patients with Hypertension - Hidayatullah, Muhammad Sodik; Hamarno, Rudi; Hidayah, Nurul; Pujiastuti, Nurul (Pusat Unggulan IPTEK Poltekkes Kemenkes Malang, 2024)
High blood pressure cannot be ignored as it can lead to complications, particularly hypertension in the elderly. If left uncontrolled, hypertension can result in complications. One non-pharmacological prevention method that is rarely known and applied by the community is complementary therapy, such as hydrotherapy and sunbathing therapy. The purpose of this study is to determine the effect of hydrotherapy techniques (warm water soaking) and sunbathing therapy on managing hypertension in the elderly. The research method used is a quasi-experimental approach with pre-test and post-test in two groups: the treatment group and the control group. Data analysis utilized paired t-test comparison, with a p-value of 0.000, indicating that there is an effect of the combination of hydrotherapy and sunbathing therapy on the blood pressure of elderly patients with hypertension. It is hoped that healthcare professionals will provide education to help prevent increased blood pressure using non-pharmacological therapies, such as the combination of hydrotherapy and sunbathing therapy.